The Effect of Service Quality and Servicescape on Customer Satisfaction in Ayam Penyet Jakarta Restaurant, Singamangaraja Branch, Medan - Lubis, Elya Puspita; Hadian, Arief; Nasution, Lukman; Harahap, Nur'ain; Lubis, Anggia Sari (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of Service Quality and Servicescape on customer satisfaction at Ayam Penyet Restaurant Jakarta, Sisingamangaraja Branch, Medan. The research method used in this research is quantitative. This research starts from pre-research conducted in January 2022 until March 2022. The data collection techniques used are observation, literature study and questionnaires. The population in this study were 2,902 consumers of Ayam Penyet Restaurant Jakarta Sisingamangaraja Branch, with a total sample of 97 consumers. The type in this research is correlational (Correlational Studies). The data analysis techniques used are validity and reliability tests, classical assumption tests, multiple linear analysis, t test (partial), F test (simultaneous), Coefficient of Determination (R2). Based on the results of the service quality t test obtained tcount > ttable (9,993> 1,985) This means that Ho is rejected and H1 is accepted, which means that service quality has a positive and significant influenceon consumer satisfactionChicken Penyet Restaurant Jakarta Sisingamangaraja Branch Medan. The results of the t-test obtained tcount > ttable (2.501> 1.985) It means that Ho is rejected and H1 is accepted which means service escapehas a positive influence on consumer satisfactionChicken Penyet Restaurant Jakarta Sisingamangaraja Branch Medan. Based on the results of the F (simultaneous) test, it shows that the value of Fcount > Ftable (90.854> 3.09). Thus, service quality and service escape simultaneously have a positive and significant effect on customer satisfaction at Ayam Penyet Restaurant Jakarta, Sisingamangaraja Branch, Medan. The results of the determination coefficient test show that the effect of service quality and servicescape variables on customer satisfaction is 0.659 or 65.9%, while the remaining 34.1% is influenced by other variables not included in this study.